The application of mindfulness-based cognitive therapy as an adjunctive therapy to alleviate depressive symptoms in post-stroke patients: a case report - Seno, Budhi Hami; Susanto, Joko; Kusuma, Wijaya (International Journal of Research in Medical Sciences, 2024)
This case report explores the application of mindfulness-based cognitive therapy (MBCT) as an adjunctive therapy to alleviate depressive symptoms in post-stroke patients. Stroke is a major global health issue, leading to significant mortality and long-term disability. Post-stroke depression (PSD) is a common complication that negatively impacts recovery and quality of life. This study aims to understand the effectiveness of MBCT in managing PSD in a patient at RSUD Dr. Moewardi. Ny. SH, a 54-year-old housewife, experienced severe depression following a stroke. Her depressive symptoms were compounded by personal challenges, including a tumultuous relationship with her husband. Over eight MBCT sessions, the patient engaged in various mindfulness exercises designed to enhance present-moment awareness and develop healthier coping mechanisms. The sessions focused on building rapport, linking thoughts and emotions, confronting negative experiences, and integrating learned techniques into daily life. The patient reported significant improvements in mood, reduced depressive symptoms, and better coping strategies. Her Hamilton depression rating scale (HDRS) score decreased, indicating a reduction in the severity of her depression. The findings suggest that MBCT can be an effective adjunctive therapy for managing depression in post-stroke patients, improving mental health through structured mindfulness and cognitive therapy techniques. This case underscores the potential benefits of MBCT in enhancing recovery and quality of life for stroke survivors. Further research is needed to standardize MBCT procedures and explore its broader application in clinical settings.